Translation Peculiarities of Economic Terms from English to Uzbek Language - Anvaronva, Mansurova Nodira (European Journal of Life Safety and Stability (2660-9630), 2022)
This article is devoted to the study of the translation peculiarities of economic terms from English into Uzbek language in terms of their nominative structure. Difficulties in translating of economic terminology are one of the main communication obstacles in the field of economic sphere. The material of the study was the English texts on economic themes. The terms were selected from newspapers such as The Wall Street Journal and The Economist. The study has practical importance, since the results can be used in classes of basic foreign language; they can also be practical materials in compiling a thematic dictionary.